Plasma Gradient of Soluble Urokinase-Type Plasminogen Activator Receptor Is Linked to Pathogenic Plasma Proteome and Immune Transcriptome and Stratifies Outcomes in Severe COVID-19 - Sarif, Jafar; Raychaudhuri, Deblina; D’Rozario, Ranit; Bandopadhyay, Purbita; Singh, Praveen; Mehta, Priyanka; Hoque, Md. Asmaul; Sinha, Bishnu Prasad; Kushwaha, Manoj; Sahni, Shweta; Devi, Priti; Chattopadhyay, Partha; et al. (Frontiers in Immunology, 2021)
Disease caused by SARS-CoV-2 coronavirus (COVID-19) led to significant morbidity and mortality world-wide. A systemic hyper-inflammation characterizes severe COVID-19 disease, often associated with acute respiratory distress syndrome (ARDS). Blood biomarkers capable of risk stratification are of great importance in effective triage and critical care of severe COVID-19 patients. Flow cytometry and next generation sequencing was done on peripheral blood cells and urokinase-type plasminogen activator receptor (suPAR) and cytokines were measured from and mass spectrometry-based proteomics was done on plasma samples from an Indian cohort of COVID-19 patients. Publicly available single cell RNA sequencing data were analyzed for validation of primary data. Statistical analyses were performed to validate risk stratification. We report here higher plasma abundance of suPAR, expressed by an abnormally expanded myeloid cell population, in severe COVID-19 patients with ARDS. Plasma suPAR level was found to be linked to a characteristic plasma proteome, associated with coagulation disorders and complement activation. Receiver operator characteristics curve analysis to predict mortality identified a cut-off value of suPAR at 1996.809 pg/ml (Odds ratio: 2.9286, 95% confidence interval 1.0427-8.2257). Lower than cut-off suPAR levels were associated with a differential expression of the immune transcriptome as well as favourable clinical outcomes, both in terms of survival benefit (Hazard ratio: 0.3615, 95% confidence interval 0.1433-0.912) and faster disease remission in our patient cohort. Thus we identified suPAR as a key pathogenic circulating molecule linking systemic hyperinflammation to the hypercoagulable state and stratifying clinical outcomes in severe COVID-19 patients with ARDS.